(untitled) (International journal of artificial intelligence, 2025)
The use of authentic videos in foreign language education has become an increasingly popular pedagogical strategy, offering learners exposure to real-life language usage and cultural contexts. Unlike scripted instructional videos, authentic materials—such as films, interviews, news segments, and vlogs are created by native speakers for native audiences. This paper explores the role of authentic videos in improving two crucial aspects of language learning: listening skills and cultural competence. Through an analysis of current research and classroom applications, it is shown that authentic videos significantly enhance learners’ listening comprehension, phonological awareness, and sociolinguistic understanding. The paper also discusses pedagogical methods for integrating authentic media and highlights challenges such as accessibility, content complexity, and learner readiness. Recommendations for educators and implications for curriculum design are offered to maximize the effectiveness of audiovisual tools in language instruction.